Redefining bladder cancer treatment: innovations in overcoming drug resistance and immune evasion - Peng Huang; Jie Wang; Zongze Yu; Jiaan Lu; Zhou Sun; Zhigui Chen (Frontiers in Immunology)
Bladder cancer is one of the most common malignancies of the urinary system and has always presented great challenges in treatment due to its intricate biological features and high recurrence rates. Although great developments were achieved in immunotherapy and targeted therapies within the last decade, therapeutic outcomes for a great number of patients remain unsatisfactory, particularly as to long-term efficacy. Review discusses the molecular mechanisms developed during the process of bladder cancer progression: genetic and epigenetic alterations, dynamics of the tumor microenvironment (TME), and dysregulation and abnormal activation of various signaling pathways—all contributing to therapeutic resistance. It is genetic mutation, especially in both low- and high-grade tumors, that, alongside epigenetic modifications, plays a considerable role in tumor aggressiveness and drug resistance. TME, comprising cancer-associated fibroblasts (CAFs), immunosuppressive cells, and different components of the extracellular matrix (ECM), orchestrates a setting that fosters tumor growth and immune evasion and confers resistance on any therapeutic regime that might be used. The review also provides an overview of PI3K/AKT and MAPK signaling pathways in the progression of bladder cancer and the development of targeted therapies against them. Further, it discusses the challenges and mechanisms of resistance to immunotherapy, including those involving immune checkpoint inhibitors. Other promising approaches include the development of new therapeutic strategies that target not only the signaling pathways but also immune checkpoints in combination therapies. This review aims to contribute to the elaboration of more effective and personalized treatment strategies by fully understanding the underlying mechanisms involved in bladder cancer.